PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KOMITMEN ORGANISASIONAL DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN - M. Zainal Arifin; Taher Alhabsji; Hamidah Nayati Utami (University of Merdeka Malang, 2018)
The purposes is to determine the effect of workload, compensation and organizational commitment to employee performance. The method is used to explanatory research by collecting information directly from the respondent, technical sampling took by stratified proporsional Random Sampling, which using the formula from Slovin to obtained sample of 116 people from a total population of 163 people. Data analysis method used to descriptive statistical analysis and inferential statistical analysis which in this study using path analysis (path analysis). The result showed that there is a significant and positive effect between work load on organizational commitment, there is no significant effect and negative between workload on employees performance, there is a significant and positive effect between compensation for organizational commitment, there is a significant and positive effect of the compensation on employees performance, and there is a significant and positive effect between organizational commitment to employees performance DOI : https://doi.org/10.26905/jbm.v5i2.2393